2016
DOI: 10.1021/acs.molpharmaceut.5b00878
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanoparticles Composed of Quaternary Amine–Tertiary Amine Cationic Lipid Combination (QTsome) for Therapeutic Delivery of AntimiR-21 for Lung Cancer

Abstract: MicroRNA-21 (miR-21) is an oncomiR that is frequently upregulated in human cancers. AntimiR-21 (AM-21) is an oligonucleotide complementary to miR-21 that is designed to inhibit its gene silencing activities. To facilitate efficient delivery of AM-21, a novel lipid nanoparticle formulation called QTsome, based on a combination of quaternary amine and tertiary amine cationic lipids, with a distinctive pH-responsive profile, was developed. QTsome/AM-21 comprising DODMA/DOTAP/DOPC/CHOL/mPEG-DPPE and AM-21 oligonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 43 publications
0
57
0
Order By: Relevance
“…The simulations in Fig 12(a) mimic this experiment; the effect of PTX is accounted for by reducing 1.4 λ Ci to 1.3 λ Ci ( i = 1, 2), and the effect of anti-miR-21 is accounted for by reducing λ m 1 to λ m 1 /2. We note however that in our model the cancer is at an earlier stage and its volume is much smaller compared to the volume of 0.8 cm 3 in [42]. …”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The simulations in Fig 12(a) mimic this experiment; the effect of PTX is accounted for by reducing 1.4 λ Ci to 1.3 λ Ci ( i = 1, 2), and the effect of anti-miR-21 is accounted for by reducing λ m 1 to λ m 1 /2. We note however that in our model the cancer is at an earlier stage and its volume is much smaller compared to the volume of 0.8 cm 3 in [42]. …”
Section: Resultsmentioning
confidence: 80%
“…Researches have observed that paclitaxel-treated cells have defects in mitotic spindle assembly, chromosome segregation and cell division [41]. Experiments in vivo by Yung et al [42] show that anti-miR-21 reduces tumor volume in NSCLC, and the combination of paclitaxel and anti-miR-21 demonstrated greater ability to reduce cancer cell proliferation than either agent administered alone. The simulations in Fig 12(a) mimic this experiment; the effect of PTX is accounted for by reducing 1.4 λ Ci to 1.3 λ Ci ( i = 1, 2), and the effect of anti-miR-21 is accounted for by reducing λ m 1 to λ m 1 /2.…”
Section: Resultsmentioning
confidence: 99%
“…While numerous nanomedicines have been developed for the delivery of anticancer drugs, there are limited studies on antipsychotic delivery. [Kim et al, ; Yung et al, ] Given the lack of the knowledge of the underlying mechanisms of psychosis, improving the delivery of current antipsychotics using nanoparticle‐based administration is a rational approach. Of all the nanomaterials, solid‐lipid and polymeric nanoparticles are the most likely to achieve success in the short term due to their long history of medical use and proven biocompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies were thus conducted to define the effectiveness of specific miRNA therapeutics for the treatment of NSCLC in animal models in vivo (Table ). AntagomiRs were employed for the inhibition of tumor promotive miR‐21‐5p, miR‐183‐5p, and miR‐206‐3p and shown to inhibit subcutaneous A549 tumors . Whereas, tumor suppressive miRNAs let‐7b‐5p or miR‐34a‐5p reduced KRAS‐activated tumor burden in vivo .…”
Section: Therapeutic Potential Of Micrornas Demonstrated In Nsclc Animentioning
confidence: 99%